The role of inclusive development and military expenditure in modulating the effect of terrorism on governance - Simplice Asongu; Jacinta C. Nwachukwu; Sara Le Roux (African Governance and Development Institute (AGDI), 2018)
Purpose- The study investigates the role of inclusive human development and military expenditure in modulating the effect of terrorism on governance. Design/methodology/approach- It is based on 53 African countries for the period 1998-2012 and interactive Generalised Method of Moments is employed. Six governance indicators from the World Bank and two terrorism variables are used, namely: domestic and transnational terrorism dynamics. Findings- The following main findings are established. There is a negative net effect on governance (regulation quality and corruption-control) when inclusive human development is used to reduce terrorism. There is a positive net impact on governance ("voice and accountability" and rule of law) when military expenditure is used to reduce domestic terrorism. Originality/value- We have complemented the sparse literature on the use of policy variables to mitigate the effect of policy syndromes on macroeconomic outcomes.
Keywords: C52; D74; F42; O38; P37; 330; Terrorism; Inclusive development; Governance; Africa